THE RELATIONSHIP BETWEEN FINANCIAL TECHNOLOGY PRODUCTS AND FINANCIAL PERFORMANCE IN THE BANKING SECTOR: EVIDENCE FROM JORDAN - Mohamed Ibrahim Mugableh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The Covid-19 pandemic affects the banking industry in both positive and negative ways. It creates threats and opportunities for the alliances between banks and financial technology (FinTech). Financial technology means the marriage or combination between finance and technology. Adopting financial technology in the banking industry has led to the expansion of automation and artificial intelligence. As a result, the customers' engagement level has improved, lowering transaction costs. Using a panel regression model with fixed effects, this paper addresses how the adoption of information and communication technology, more precisely, financial technology products, could affect the financial performance of the banking industry in Jordan. The financial technology products include the internet, broadband, mobile, automated transfer machines, and branches. The results show that financial technology products in the banking sector improve financial performance. In addition, a positive relationship has been found between financial technology products and banking system stability.